The science and art of dermal fillers for soft-tissue augmentation - Carruthers, Jean; Cohen, Steven R; Joseph, John H; Narins, Rhoda S; Rubin, Mark (Journal of drugs in dermatology, 2009)
Our expanding understanding of the physiological and immunological conditions of the skin and, in particular, the aging face, has prompted a growing field of aesthetic technology. Restorative procedures are taking advantage of improved and refined biotechnology, which continues to evolve at a rapid pace. Whereas surgical correction of skin laxity was the norm in years past, there are now many topical options available to encourage healthy, youthful skin, and an ever-growing, increasingly perfected depot of minimally invasive, injectable dermal volumizers and stimulators, collectively referred to as dermal fillers. The growth indicators for this market are as striking as the science. However, successful use of dermal fillers is not only a function of the quality of science leading to improved biocompatibility but also the "art" of client selection, filler application and vigilant follow up. Even the "ideal" filler is subject to unique interactions with both the practitioner and the patient. This article presents a review of the safety and efficacy of the most commonly used dermal fillers with emphasis on those approved for facial aesthetics. The subtleties of improved filler technologies that impact tissue acceptance and reaction, measures of effectiveness and a comparison of wrinkle-reduction outcomes, the nature and incidence of acute and chronic tissue reaction, and a discussion of recommended or preferred filler applications are presented.